Pengaruh Konten Instagram Mills Terhadap Minat Beli: Survei Pada Followers Instagram @Millssportid - Mohamad Rifky Rachmadillah; Oktaviana Purnamasari (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
Mills is a sports brand that also offers a wide range of products with the lastest quality and technology, whict naturally piques the interest of the public in Mills and generates purchasing intent among consumers towards Mills’ products. The purpose of this research is to determine the extent of the influence of Mills’ Instagram content on purchase intent. The theories utilized in this study include Hermawan’s 2012 marketing communication theory, as well as Kotler & Keller’s Attention, Interest, and Desire theory on the Purchase Intent variable. Miles’2014 theory is applied to the Instagram Content variable, encompassing profile name, comments or feedback, and captions or descriptions. This researh adopts a quantitative approach through a survey method conducted on 85 respondents who follow @millssportid on instagram, selected using simple random sampling technique. The results of this study indicate a high influence of 73,9% of Mills’ instagram content on purchase intent, with the remaining 26,1% influenced by unexamined variables in this research.